ТАЪЛИМ ВА ТАРБИЯ ЖАРАЁНИДА ЎҚУВЧИ-ЁШЛАР МАЪНАВИЯТИНИ ОММАВИЙ АХБОРОТ ВОСИТАЛАРИ АСОСИДА ШАКЛЛАНТИРИШ ТЕХНОЛОГИЯСИ - Тайлакова, Ш.Н. (SCIENCE and SOCIETY, 2016)
The article is devoted to the study of forming young students’ spirituality on the basis of mass media in the proces of education and upbringing as the basic task of today.
Keywords: civil society; education; upbringing; ideological education; young students; MASS-MEDIA; television; radio; Internet